INTERNALIZING THE VALUE OF MULTICULTURAL EDUCATION THROUGH ISLAMIC RELIGIOUS EDUCATION IN ELEMENTARY SCHOOL - Madkan, Madkan; Mumtahana, Lusia (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Writing this article aims to analyze and describe the internalization of the values of Multicultural Education with PAI Learning in State Elementary School 1 Balun Village, Turi District, Lamongan Regency. This research was conducted at SDN 1 Pancasila Village Balun Turi Lamongan. This research was conducted using a qualitative method with a phenomenological study approach, and data collection through interviews, and documents. data analysis using the Miles and Huberman model, namely data reduction, data display, and conclusion verification. The results of this study Researchers found three forms of internalized values including the value of tolerance, the value of cooperation, and ukhuwah Basyariah and Wathoniah. Internal supporting factors: comprehensive educational curriculum and textbooks with multicultural content. The external supporting factor is the community that actively participates in providing an understanding of the importance of mutual respect between religious communities.